The gastro-intestinal helminth parasites of the swamp wallaby, Wallabia bicolor (Desmarest) (Marsupialia: Macropodidae), and their regional distribution. Issue 2 (2nd July 2016) - Beveridge, Ian
ABSTRACT: The gastro-intestinal helminth parasite community of the swamp wallaby, Wallabia bicolor (Desmarest) (Marsupialia: Macropodidae) is reviewed based on published and previously unpublished data, covering its entire geographical range. The diversity recorded is higher than in previous studies and with substantial differences between northern and southern parasite communities. This difference is attributable in part to host-specific parasite species, but is due mainly to species acquired from sympatric macropodid hosts, which differ substantially between northern and southern regions. Additionally, helminth species were identified with primarily southern distributions but with occurrences at a low prevalence in northern regions. Diversity was greater in southern populations of the host. It is predicted that additional helminth parasites are likely to be found in W. bicolor, but that these will be either species with a highly localised distribution, of which several have already been reported, or occasional transfers from related confamilial hosts. The study emphasises the significance of examining the parasites of a host over its entire geographical range rather than at more local scales.